Development of Ethnomathematics-Based Textbooks of the Sasak Tribe on the Circumference and Area of Flat Shapes for Grade V Elementary School - Rini Musliana; Muhammad Turmuzi; Iva Nurmawanti (Yayasan Insan Mulia Bima, 2025)
The independent curriculum emphasizes the provision of learning tools and the importance of implementing contextual learning through the integration of local culture. This research aims to develop ethnomathematics-based textbooks for the Sasak Tribe on the material of the circulation and area of flat buildings in class V at SDN 38 Cakranegara by meeting valid and practical criteria. This type of research uses 4-D (Define, Design, Develop, and Disseminate) development research. The subject of this study is a grade V student at SDN 38 Cakranegara and the object of this research is an ethnomathematics-based textbook of the Sasak Tribe on the material of the circumference and flat building area of class V. Data collection techniques are carried out through filling out questionnaires of material experts and media experts as well as questionnaires of student and teacher responses. Data analysis techniques use qualitative and quantitative methods. The results of this study indicate that the ethnomathematics-based textbooks of the Sasak Tribe on the material of the circumference and area of the flat shapes for grade V has met the criteria of being very valid and very practical with a percentage of material validity of 92.81%, media validity of 92.37%, a percentage of practicality based on the results of the student’s response questionnaire of 81% and a teacher response questionnaire of 98.33%.